Polyhexamethylene Biguanide and Nadifloxacin Self-Assembled Nanoparticles: Antimicrobial Effects against Intracellular Methicillin-Resistant Staphylococcus aureus. - Kamaruzzaman, Nor Fadhilah; de Fatima Pina, Maria; Chivu 4, Alexandru; Good, Liam (WOS/ SCOPUS, 2018)
The treatment of skin and soft tissue infections caused by methicillin-resistant Staphylococcus aureus (MRSA) remains a challenge, partly due to localization of the bacteria inside the host’s cells, where antimicrobial penetration and efficacy is limited. We formulated the cationic polymer polyhexamethylene biguanide (PHMB) with the topical antibiotic nadifloxacin and tested the activities against intracellular MRSA in infected keratinocytes. The PHMB/nadifloxacin nanoparticles displayed a size of 291.3 ± 89.6 nm, polydispersity index of 0.35 ± 0.04, zeta potential of +20.2 ± 4.8 mV, and drug encapsulation efficiency of 58.25 ± 3.4%. The nanoparticles killed intracellular MRSA, and relative to free polymer or drugs used separately or together, the nanoparticles displayed reduced toxicity and improved host cell recovery. Together, these findings show that PHMB/nadifloxacin nanoparticles are effective against intracellular bacteria and could be further developed for the treatment of skin and soft tissue infections.